2019
DOI: 10.1177/0038040718824095
|View full text |Cite
|
Sign up to set email alerts
|

The Social Pipeline: How Friend Influence and Peer Exposure Widen the STEM Gender Gap

Abstract: Individuals' favorite subjects in school can predetermine their educational and occupational careers. If girls develop weaker preferences for science, technology, engineering, and math (STEM), it can contribute to macrolevel gender inequalities in income and status. Relying on large-scale panel data on adolescents from Sweden (218 classrooms, 4,998 students), we observe a widening gender gap in preferring STEM subjects within a year (girls, 19 to 15 percent; boys, 21 to 20 percent). By applying newly developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 81 publications
7
92
1
Order By: Relevance
“…For instance, in course transcript data from the Adolescent Health and Academic Achievement Study (AHAA), high school female students were more likely to take more advanced level math courses in the year after being enrolled in a course with other same-sex peers who have taken higher level math coursework (Frank et al, 2008). In the Swedish subset of the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU), students’ favorite subjects were influenced by friends’ preferences (friend influence) and classroom peers’ preferences (peer exposure; Raabe et al, 2019). Specifically, exposure to female classmates who have a STEM-favorite subject has a strong positive effect on girls’ individual STEM preferences (Raabe et al, 2019).…”
Section: Social Capital Benefits Stem Education: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in course transcript data from the Adolescent Health and Academic Achievement Study (AHAA), high school female students were more likely to take more advanced level math courses in the year after being enrolled in a course with other same-sex peers who have taken higher level math coursework (Frank et al, 2008). In the Swedish subset of the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU), students’ favorite subjects were influenced by friends’ preferences (friend influence) and classroom peers’ preferences (peer exposure; Raabe et al, 2019). Specifically, exposure to female classmates who have a STEM-favorite subject has a strong positive effect on girls’ individual STEM preferences (Raabe et al, 2019).…”
Section: Social Capital Benefits Stem Education: Evidencementioning
confidence: 99%
“…In the Swedish subset of the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU), students’ favorite subjects were influenced by friends’ preferences (friend influence) and classroom peers’ preferences (peer exposure; Raabe et al, 2019). Specifically, exposure to female classmates who have a STEM-favorite subject has a strong positive effect on girls’ individual STEM preferences (Raabe et al, 2019).…”
Section: Social Capital Benefits Stem Education: Evidencementioning
confidence: 99%
“…Friendships made during the years of education have an exceptional effect on students, which they may carry on to adulthood. From early primary school to university, peer relations have been linked to students' psychological well-being 6 , health-related behavior 7,8 , bullying and negative ties 9,10 , peer perceptions 11,12 , academic subject preferences 13,14 , and academic success or failure 15,16 .…”
mentioning
confidence: 99%
“…More generally, empirical evidence suggests that parents and peers affect the educational and occupational aspirations of youth (Sewell et al, 1970;Morgan, 1998;Bozick et al, 2010). Studies have shown that students adjust their STEM-preferences in high school to those of their friends (Raabe et al, 2019).…”
Section: State Of Researchmentioning
confidence: 99%